Time to Shift from Systems Thinking-Talking to Systems Thinking-Action; Comment on "Constraints to Applying Systems Thinking Concepts in Health Systems: A Regional Perspective from Surveying Stakeholders in Eastern Mediterranean Countries" - Bev J. Holmes; Kevin Noel (Kerman University of Medical Sciences, 2015)
A recent International Journal of Health Policy and Management (IJHPM) article by Fadi El-Jardali and colleagues makes an important contribution to the literature on health system strengthening by reporting on a survey of healthcare stakeholders in Low- and Middle-Income Countries (LMICs) about Systems Thinking (ST). The study's main contributions are its confirmation that healthcare stakeholders understand the importance of ST but do not know how to act on that understanding, and the call for collective action by the global community of systems thinkers committed to healthcare improvement. We offer three basic considerations for next steps by this community, derived from our recent work in ST and the related field of Knowledge Translation (KT): resist the temptation to adopt a reductionist approach; recognize not everyone needs to understand ST; and do not wait for everything to be in place before getting started.